Competenze mediaeducative e tecnologie di comunità. Nuove direzioni per il lavoro socioeducativo territoriale - Pasta, Stefano; Rondonotti, Marco (Rivista Italiana di Educazione Familiare, 2020)
The subject of this paper are, in the light of the new ecosystem of the infosphere, transversal media educational competences, related to Information Literacy, which are central to the positive outcome of the territorial socio-educational activities carried out by working groups. The paper presents the case study “Humans of Rizzo-HoR”, in which this perspective is the basis of a territorial social animation, proposed in a suburb of Novara by local authorities with CREMIT of Catholic University. The basic logic of the educational intervention consists in onlife and in the so-called «community technologies» (Rivoltella, 2017a, passim), and in the participation in realizing videos and, in general, in creating a narration emerging “from below”, since the methodology used consists in storytelling. The analysis shows that the convergence between the sphere of communication and that of social work is real and strong. This implies a rethinking of the relationship of educational operators with digital media, to include in their training the concept of media literacy and “new alphabets” for post-media society.